Influence of initial pH of the growing medium on the activity, production and expression profiles of laccases produced by Pleurotus ostreatus in submerged fermentation - Díaz, Rubén; Téllez-Téllez, Maura; Bibbins-Martínez, Martha D; Sánchez, Carmen; Díaz-Godínez, Gerardo; Soriano-Santos, Jorge (Electronic Journal of Biotechnology, 2013)
Background: Enzymatic activity and laccase isoenzymes number of Pleurotus ostreatus grown in different pH values of the growing medium in submerged fermentation and incubated in buffer solutions of different initial pH values were determined. The expression profiles of five laccase genes (Lacc1, Lacc4, Lacc6, Lacc9 and Lacc10) in these cultures were also studied. Results: The highest laccases activity was obtained in cultures grown at initial pH of 4.5 and the lowest in cultures grown at initial pH of 8.5. Isoenzyme profiles were different in all the cases. Lacc1, Lacc4, Lacc6 and Lacc10 were expressed in all the cultures. Conclusions: The initial pH of the growing medium is an important factor for regulating the expression of laccase genes, having an effect on the activity and on the laccase isoenzymes number produced by P. ostreatus in SmF. This is the first report on the influence of different initial pH values of the growing medium on the laccases activity, laccase isoenzymes number and laccases expression profiles of P. ostreatus grown in submerged fermentation.